2013
DOI: 10.1016/j.exphem.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the sodium-dependent phosphate import protein, PiT1 (SLC20A1), have a severe defect in terminal erythroid differentiation and early B cell development

Abstract: Phosphate is critical in multiple biological processes (phosphorylation reactions, ATP production, and DNA structure and synthesis). It remains unclear how individual cells initially sense changes in phosphate availability and the cellular consequences of these changes. PiT1 (or SLC20A1) is a constitutively expressed, high-affinity sodium-dependent phosphate import protein. In vitro data suggest that PiT1 serves a direct role in mediating cellular proliferation; its role in vivo is unclear. We have discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…Recently, functions of PiT1 that are independent of its role in phosphate transport have been identified. PiT1 is involved in regulation of proliferation, density, and adhesion (Beck et al, 2009;Byskov et al, 2012;Kongsfelt et al, 2014), embryonic mouse liver development (Beck et al, 2010), tumor necrosis factor (TNF)-induced apoptosis (Sala€ un et al, 2010), and erythroid and B cell differentiation (Forand et al, 2013;Liu et al, 2013). How PiT1 drives these different functions is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, functions of PiT1 that are independent of its role in phosphate transport have been identified. PiT1 is involved in regulation of proliferation, density, and adhesion (Beck et al, 2009;Byskov et al, 2012;Kongsfelt et al, 2014), embryonic mouse liver development (Beck et al, 2010), tumor necrosis factor (TNF)-induced apoptosis (Sala€ un et al, 2010), and erythroid and B cell differentiation (Forand et al, 2013;Liu et al, 2013). How PiT1 drives these different functions is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Salaun et al showed that a Pi uptake-deficient PiT-1 mutant reduced the rate of apoptosis in HeLa cells treated with Tumor Necrosis Factor-α [23]. Finally, PiT-1 regulation of hematopoietic stem cell differentiation was found to be Pi uptake-independent [27, 28]. However, none of those studies identified the cell signaling pathway required for transport-independent PiT-1 functions.…”
Section: Discussionmentioning
confidence: 99%
“…Pit-1 and Pit-2 may have redundant roles in vascular calcification [21] and bone mineralization [22], according to two recent reports showing enhanced Pit-2 expression under conditions in which Pit-1 expression is compromised. However, the functions of the two proteins do not entirely overlap as evidenced by studies showing severe defects in erythroid differentiation in Pit-1-deficient animals [23].…”
Section: Type II Sodium Phosphate Cotransportersmentioning
confidence: 95%